(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Previous research on the development of normal air cooler has been conducted into a proposed four-door air cooler. The results indicated that the effectiveness of the proposed air cooler (75.4% - 30.3%) was higher than the effectiveness of the normal air cooler (70.4% - 15.2%) at temperatures of (42oC - 33oC) but the effectiveness of both air coolers corresponded to the high temperature (42oC - 43oC). As well as the relative humidity of the air coming out of the proposed air cooler was higher than the normal air cooler at times of high temperature degrees (42oC - 33oC). However, the case is reversed at times of temperature degrees higher than (42oC). This means that the relative humidity of the air coming out of the proposed air cooler was lower. Therefore, it was necessary to study the effect of water flow on the cooling effectiveness in the proposed air cooler. A four-door air cooler with variable flow rate was designed and manufactured. A practical study and test was carried out and the optimal flow of water in the air cooler was determined to be 1800 L/hr. Another practical study and test was carried out to compare the performance of the normal air cooler against the proposed one with optimum water flow. The results showed that the proposed air cooler with the optimal water flow was the most effective and the most reduction of the temperature of the air inside the air cooler at various times of the day. It was noticeable that the difference between them increased in hot weather hours. The air coming out of the proposed air cooler with optimal water flow was more humid than the normal air cooler at different times of the day. The results indicate that the performance of the proposed air cooler with optimal flow is better than normal air cooler performance in most weather conditions in Iraq.